2009
DOI: 10.1080/09712119.2009.9706996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Honey inPseudomonas aeruginosaInduced Stromal Keratitis in Rabbits

Abstract: To evaluate the healing effect of honey in Pseudomonas aeruginosa induced keratitis, 26 eyes of 26 white New Zealand Rabbits were experimentally infected with P. aeruginosa. Ten eyes were treated with a 90% concentration of natural honey, 10 with topical 0.3% ciprofloxacin and 6 eyes were left untreated. After one week, the eyes were enucleated and evaluated clinically and microscopically. All corneas showed a n opaque stromal infiltration at least 20 h post injection with progressive expansion only in the unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…However, we found that there was a similar treatment benefit in all three groups with a reduction of median CFU on day seven. This finding is inconsistent with the study done by Nejabat et al who found that topical 90% concentrated natural honey was equally effective as ciprofloxacin 0.3% at treating Pseudomonas-induced keratitis in rabbit eyes and that both treatments led to a significant reduction in the number of bacteria compared to controls [23].…”
Section: Discussioncontrasting
confidence: 72%
“…However, we found that there was a similar treatment benefit in all three groups with a reduction of median CFU on day seven. This finding is inconsistent with the study done by Nejabat et al who found that topical 90% concentrated natural honey was equally effective as ciprofloxacin 0.3% at treating Pseudomonas-induced keratitis in rabbit eyes and that both treatments led to a significant reduction in the number of bacteria compared to controls [23].…”
Section: Discussioncontrasting
confidence: 72%
“…Medically regulated pure antibacterial honeys may have numerous practical advantages when used in corneal disease. These include a rapid clinical effect (Figures , and ), preservative‐free, long shelf‐life, unaffected by UV, storage at room temperature, low relative cost and relative abundance . Pure, raw honey is non‐toxic to the ocular surface, even with chronic use on a compromised ocular surface and allergy to honey is rare .…”
Section: Discussionmentioning
confidence: 99%
“…These include a rapid clinical effect (Figures 1, 2 and 3), preservative-free, long shelf-life, unaffected by UV, storage at room temperature, low relative cost and relative abundance. [1][2][3][4][5][6][7][8][9][10][11][12][13] Pure, raw honey is non-toxic to the ocular surface, even with chronic use on a compromised ocular surface 4,6,7 and allergy to honey is rare. [1][2][3] High-efficacy antibacterial Leptospermum spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations